2016
DOI: 10.1186/s12950-016-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased adipose tissue expression of TLR8 in obese individuals with or without type-2 diabetes: significance in metabolic inflammation

Abstract: BackgroundThe innate immune Toll-like receptors (TLRs) 2/4 are important players in chronic low-grade inflammation called metabolic inflammation in obesity and type-2 diabetes (T2D). While TLR2/4 expression changes associated with metabolic inflammation are known, the adipose tissue expression of endocytic TLR8, which is expressed by all major macrophage subsets, remain unclear. We, therefore, determined the TLR8 mRNA/protein expression in the adipose tissue samples from lean, overweight, and obese individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…In line with this finding, increased expression of TLRs 1-9 and TLRs 11-13 was reported in two murine models of obesity [55]. Whereas in obese/T2D individuals, we have already reported the increased expression of several TLRs including TLR-2, -4, -7, -8, and -10 [28,[56][57][58]. The present data show the congruence between adipose tissue expression of IRF5 and most TLRs in obesity/T2D.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this finding, increased expression of TLRs 1-9 and TLRs 11-13 was reported in two murine models of obesity [55]. Whereas in obese/T2D individuals, we have already reported the increased expression of several TLRs including TLR-2, -4, -7, -8, and -10 [28,[56][57][58]. The present data show the congruence between adipose tissue expression of IRF5 and most TLRs in obesity/T2D.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with this argument, it was shown that the visceral adipose tissue expression of several TLRs (TLR1, TLR4, TLR5, TLR8, TLR9, & TLR12) and downstream signaling molecules (MyD88, IRFs, NF-κB & STAT-1) was higher in diet-induced obese mice than leptin-deficient ob/ob mice [18]. Also in humans, increased expression of TLR2, TLR3, TLR4, TLR5, TLR7, and TLR8 was reported in obesity/T2D [14, 19, 20]. Among all TLRs, little is known about ligand(s) and function of TLR10.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sindhu et al ( 41 ) revealed that CD86 protein expression was significantly enhanced in adipose tissue samples obtained from patients with obesity. Furthermore, CD86 has been demonstrated to be positively correlated with the levels of pro-inflammatory cytokines in adipose tissues, including IL-18, IL-18R and TLR8 ( 42 , 43 ). Vitamin D supplementation, which decreases the expression of CD86 in the spleen, has been proposed as a treatment option to alleviate high-fat diet-induced obesity ( 44 ).…”
Section: Discussionmentioning
confidence: 99%